Pengelolaan Sekolah Berbasis Religi (Studi Situs SDIT Muhammadiyah Al-Kautsar Gumpang Kartasura Sukoharjo - Asmawan, Moh. Chairil, Prof. Dr. Sutama, M.Pd (2015)
This study aims to : ( 1 ) describe the management of the curriculum ; ( 2 ) describe the management of the student ; ( 3 ) describe the infrastructure . This research is a qualitative ethnographic approach . Implementation research in SDIT Muhammadiyah Al - KawtharGumpangKartasura . Informants selected is the principal, teachers and students . Technical descriptive data analysis is inductive . The validity of the data source using triangulation techniques , as well as interviews with informants . This study has three conclusions .( 1 ) Management of faith-based curriculum that starts from planning the curriculum implemented at the beginning of the year . Using the two systems , namely official curriculum and religious curriculum . ( 2 ) management of the program the students are done with habituation in accordance with the philosophy of religion . Training students performed in a variety of fields, including academic and non - academic ; ( 3 ) management of school facilities and infrastructure -based religion . The school principal appointed a teacher in charge of school facilities and infrastructure . Event management infrastructure is divided into sections such as : planning , procurement infrastructure inventory records , maintenance of facilities and infrastructure , the use of school facilities and infrastructure . Keywords: curriculum; students; means infrastructures; school